(untitled) (Research, Society and Development, 2021)
Objective: to analyze the adverse effects of using Minoxidil in patients with androgenic Alopecia. Methods: An integrative literature review was carried out, a method that allows a synthesis of the knowledge obtained in a certain number of studies and its incorporation in the form of applicability of the results obtained from significant studies in the practice of evidence-based research. The research question “What are the adverse effects of using Minoxidil in androgenetic alopecia?” Was used. Then, a search was conducted in the international database Medical Publisher (PUBMED) and in the Virtual Health Library (VHL) with the keywords “Minoxidil” AND “Alopecia” AND “Adverse effects”. Results: the most common adverse effects with the use of topical Minoxidil are Hypertrichosis, itchy scalp, contact dermatitis and erythema. Dry skin, increased sensitivity, dandruff production have also been reported. Some less frequent symptoms were systemic cardiovascular signs, such as hypotension and syncope. Conclusion: Treatment with Minoxidil in both it’s topical and systemic conformation for Androgenetic Alopecia is an effective and safe measure for hair growth, with adverse effects that can be well controlled and tolerated.